STUDENTS’ MASTERY OF PHRASAL VERBS AND THEIR READING COMPREHENSION ABILITY - Zaitun, Zaitun; Hadi, Muhamad Sofian; Falaq, Shifa Fadila Nurul (Universitas Muhammadiyah Palembang, 2021)
The objective of this research is to find out whether or not there was correlation between students’ mastery of phrasal verbs and their reading comprehension ability. This research used quantitative method with the research design of correlational study. The subject of this research was 2nd semester students of English Teacher Education, Muhammadiyah University of Jakarta which consisted of 41 students. In collecting the data, the writer used phrasal verbs test and reading comprehension test as the instruments. The data were computed statistically by using Pearson Product Moment SPPS 20. The result showed that there was a positive medium correlation in which the coefficient correlation “rvalue” (0.496) was higher than the value of rtable (0.308) with the level of significance 5% (0.496 > 0.308).